Impact of COVID-19 on International Retail Company on Spanish Market: Case of “Carrefour” - Elena V. KOLGANOVA; Dmitry I. BABIY; Alexander I. BABIY (Communications of International Proceedings, 2020)
The aim of the article is to analyze the impact of the COVID-19 on the operations of the retail company on Spanish market. The international retailer Carrefour was chosen as an object as it has a considerable effect on the Spanish retail market. This is one of the companies that managed to rebuild its activities and adapt in the shortest time to the situation. Despite the fact that in some countries the company had to temporarily close its non-food departments, it faced significant increase in the sphere of e-commerce and food sales as it could partnerships with transportation companies and meet the changing needs of the customers in the period of Pandemic. In the article authors pay special attention to the analysis of the company’s environment (3C’s analysis and SWOT-analysis) and to its distribution and logistics operations on the Spanish market.
Keywords: Pandemic COVID-19; Retail Company; Spanish Retail Market.